Functional improvement by body-powered 3D-printed prosthesis in patients with finger amputation: Two case reports. Issue 25 (24th June 2022) - Lee, Min-Yong; Lee, Seung Hak; Leigh, Ja-Ho; Nam, Hyung Seok; Hwang, Eun Young; Lee, Jung Yeon; Han, Sol; Lee, Gangpyo
Abstract: Rationale: The most common upper limb amputations are finger amputations, resulting in functional limitations that lead to problems with activities of daily living or job loss. For many years, prosthetic options for finger amputations have been limited to passive prostheses. In many countries including South Korea, body-powered finger prostheses have rarely been prescribed due to high cost, lack of experience of physicians and prosthetists, low interest and no coverage by insurance benefits. We report 2 cases of work-related finger amputations in patients who received body-powered 3D-printed finger prostheses. Patient concerns and diagnosis: Patient 1 was a 25-year-old woman with second and third finger amputations at the proximal interphalangeal level. Patient 2 was a 26-year-old man who sustained a second finger amputation at proximal interphalangeal level. Interventions: We created body-powered 3D-printed finger prostheses that mimicked distal interphalangeal joint motion through patient-driven metacarpophalangeal joint motion using a string connected to a wrist strap and a linkage system. The source code "Knick Finger" was downloaded from e-NABLE. Outcomes: After 1 month of prosthesis training, both patients were satisfied with the prostheses and showed improved performance in patient-derived goals of cooking (patient 1) and typing on a computer (patient 2). Lessons: Over the past decade, significant advances have been made in 3D-printed prosthetics owing to their light weight, low cost, on-site fabrication, and easy customization. Although there are still several limitations in the general application of 3D-printed finger prostheses, our study suggests that for patients with finger amputations, body-powered 3D-printed finger prostheses have high potential as an additional prosthetic option to the existing passive cosmetic prostheses.